Perancangan Dashboard dan Forecasting Asuransi Properti dengan Metode Holt-Winters Triple Exponential Smoothing - Tony Tony; Ruach Sakadewa (Departement of Mathematics Education, 2023)
Insurance is a mechanism for transferring the impact of a risk to another party. PT. XYZ is an insurance company based in Bandung and focuses on property insurance products. There is a problem where this company does not have an interactive data visualization that can show the company's performance. For this reason, researchers created a solution in the form of an interactive dashboard accompanied by forecasting using the Holt-Winters Triple Exponential Smoothing method to predict the number of registered policies in the future. The addition of secondary data from the website of the National Disaster Management Agency (BNPB) to display the distribution of the types of natural disasters that occur. All data obtained has regional boundaries in West Java and ranges from 2016 to 2022. From the research that has been carried out, a dashboard has been produced that can display visualizations of the spread of disasters, visualization of graphs comparing the number of policies and claims, visualization of insurance renewal percentages, visualization of the top 5 occupations property, visualization of the top 5 property insurance products, KPI sales, and forecasting results with an indication of a Mean Absolute Percentage Error (MAPE) of 20.22% which is indicated as feasible.